Satellite Fe3O4@SiO2–Au SERS probe for trace Hg2+ detection. Issue 77 (2nd August 2016) - Sun, Zhenli; Du, Jingjing; Lv, Bo; Jing, Chuanyong
Abstract : Core–satellite Fe3 O4 @SiO2 –Au for the detection of Hg 2+ based on a "turn-off" SERS strategy using congo red as a Raman reporter. Abstract : Plasmonic core–satellite Fe3 O4 @SiO2 –Au (FA) was synthesized for Hg 2+ detection based on the "turn-off" SERS strategy. The functionalization of FA simply included the adsorption of congo red (CR) to FA through a PDDA linker. In the presence of Hg 2+, CR molecules are released from the substrate, thus generating a decreased peak intensity in the observed Raman spectra. This "turn-off" effect serves as the basis for the determination of trace Hg(ii ) with a detection limit of 1 × 10 −8 M. The strong interaction between Hg 2+ and the SERS substrate was confirmed by zeta potential and SEM-EDS analysis. The XANES results show that 94% of Hg on the substrate was reduced to Hg 0, indicative of an Hg–Au amalgam formation. The interference from other metal ions and humic acids commonly encountered in the environment was negligible. This FA–CR SERS platform is a promising tool for monitoring mercury ions in environmental applications.